IDENTITAS KEBANYUMASAN DALAM PENGGUNAAN BAHASA DI RUANG PUBLIK - Dwiana Anugrahita; Sudartomo Macaryus (Universitas Sarjanawiyata Tamansiswa, 2015)
This study aims to describe the diversity of language use and identity which looks at the use of language in public space as a reflection kebanyumasan identity. This research was done in three phases namely data providing, data analyzing, and presenting data analysis. The characteristic of Banyumas language was used as samples found in Banjarnegara, Purbalingga, Banyumas, Cilacap, and Kebumen area. The result of this research showed that varieties of language usage at the public place could be classified based on the poster, street banners, billboards, and signposts found in Banyumas area. The characteristic of language usages in Banyumas area includes some language usage aspects, namely lexical-semantic, morphology, and syntax.Â Â Â